2008
DOI: 10.1007/s10517-008-0230-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal and neonatal cadmium intoxication on the intensity of lipid peroxidation and activity of glutathione system in progeny of albino rats

Abstract: Oral treatment of pregnant or lactating rats with Cd(NO3)2 in a dose of 2 mg/kg increased plasma and erythrocyte levels of MDA and reduced glutathione, activities of glutathione-S-transferase, glutathione reductase, and gamma-glutamyl transferase in their 4-month-old progeny. Changes in the function of glutathione system and LPO intensity after cadmium intoxication during the neonatal were less pronounced than after prenatal exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, exposure to Cd also causes necrotic cell death, characterized by cell membrane disintegration followed by dissemination of intracellular contents (Ishido et al 2002;Sancho et al 2006). Both apoptosis and necrosis can be induced by increased accumulation of ROS (Fleury et al 2002;Hossain et al 2009), and increased lipid peroxidation after Cd-exposure has been shown several times (Hussain et al 1987;Yiin et al 2000;Jurczuk et al 2004;Babu et al 2006;Kotelnikova et al 2008;Slyuzova et al 2008). A disturbed redox balance can, however, also induce uncontrolled cell proliferation and Cd carcinogenicity seems to be crucially mediated by the production of ROS (Waisberg et al 2003).…”
Section: Cadmium: An Oxidative Challengementioning
confidence: 99%
“…However, exposure to Cd also causes necrotic cell death, characterized by cell membrane disintegration followed by dissemination of intracellular contents (Ishido et al 2002;Sancho et al 2006). Both apoptosis and necrosis can be induced by increased accumulation of ROS (Fleury et al 2002;Hossain et al 2009), and increased lipid peroxidation after Cd-exposure has been shown several times (Hussain et al 1987;Yiin et al 2000;Jurczuk et al 2004;Babu et al 2006;Kotelnikova et al 2008;Slyuzova et al 2008). A disturbed redox balance can, however, also induce uncontrolled cell proliferation and Cd carcinogenicity seems to be crucially mediated by the production of ROS (Waisberg et al 2003).…”
Section: Cadmium: An Oxidative Challengementioning
confidence: 99%
“…Cytotoxicity of Cd is mediated by both apoptosis and necrosis. These two mechanisms are caused by oxidative stress resulting from increased accumulation of ROS (Fleury et al, 2002; Hossain et al, 2009) and increased LPO after exposure to Cd (Kotelnikova et al, 2008; Slyuzova et al, 2008; Tezcan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%